2009
DOI: 10.1139/y09-039
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide attenuates the pathogenesis of pulmonary fibrosis induced by bleomycin in rats

Abstract: The present study investigated the role of the endogenous cystathionine gamma-lyase (CSE) / hydrogen sulfide pathway in the pathogenesis of pulmonary fibrosis. Rats treated with intratracheal bleomycin were exposed either to the H2S donor NaHS or to saline. The results on day 7 showed that plasma H2S concentration and pulmonary CSE activity (H2S production rate) were significantly lower in rats treated with bleomycin and saline (fibrosis-alone) than in controls, whereas on day 28 plasma H2S concentration was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 29 publications
0
45
0
6
Order By: Relevance
“…21 Moreover, low doses of NaHS (78 and 392 μg/kg/day body weight, twice daily) also reduced pulmonary fibrosis induced by bleomycin. 11 Previous studies demonstrated that H 2 S level in vertebrate blood varied from 10–300 μmol/l by the methylene blue assay. 22, 23 Using a sensitive fluorescent probe, 24 we found the plasma H 2 S level in normal rat was ∼30–40 μmol/l, whereas its counterpart in the UUO rat was 20–30 μmol/l.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Moreover, low doses of NaHS (78 and 392 μg/kg/day body weight, twice daily) also reduced pulmonary fibrosis induced by bleomycin. 11 Previous studies demonstrated that H 2 S level in vertebrate blood varied from 10–300 μmol/l by the methylene blue assay. 22, 23 Using a sensitive fluorescent probe, 24 we found the plasma H 2 S level in normal rat was ∼30–40 μmol/l, whereas its counterpart in the UUO rat was 20–30 μmol/l.…”
Section: Discussionmentioning
confidence: 99%
“…10 Emerging evidence also demonstrates that H 2 S exhibits antifibrotic effects in the lung, heart, and liver. 11, 12, 13 Furthermore, H 2 S bears some similarities to the other two gaseous molecules, nitric oxide and carbon monoxide, both of which protect the kidney from renal fibrosis. 14, 15 Taken together, we hypothesize that H 2 S may attenuate renal fibrosis.…”
mentioning
confidence: 99%
“…The kidney also plays a major role in Hcy metabolism [31] and plasma total Hcy increases with the declines of renal function [29]. Hcy, however, in the mammalian tissue can be metabolized further using three endogenous enzymes (CBS, CSE and 3MST) to produce H 2 S. Although H 2 S has been known for decades as a toxic gas with intoxication effects on the central nervous system and respiratory system, recently it has been documented as an important physiological gaseous molecule with antioxidant [13,18], antihypertensive [32], anti-inflammatory [10,16] and antifibrotic [33,34] properties.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 S is a newly identified endogenous gaseous signaling molecule. Evidences have suggested that H 2 S is protective against inflammation in various fibrosis-related diseases [5,6,7,20,21]. We previously demonstrated, at a relatively low dose (56 µg/kg/day), NaHS protected against UUO by attenuating the infiltration of macrophages and the expression of tumor necrosis factor-alpha in renal cortex [7].…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, modulation of endogenous H 2 S through either its enzymatic inhibitors or H 2 S-donor compounds represented therapeutic potential for a variety of human diseases related with chronic inflammation and organ fibrosis. Recent evidences demonstrate that exogenous H 2 S attenuates aortic-coarctation-induced cardiac hypertrophy and fibrosis [5], bleomycin-induced pulmonary fibrosis [6], unilateral ureteral obstruction (UUO)-induced kidney fibrosis [7] and carbon tetrachloride-induced cirrhosis [8]. The underlying anti-fibrotic mechanisms of H 2 S may be explained by inhibiting the activation and migration of inflammatory cells as well as myofibroblasts, subsequently attenuating the production of pro-inflammatory cytokines and extracellular matrix (ECM) accumulation [8,9,10].…”
Section: Introductionmentioning
confidence: 99%